Answer:
[tex]y=x^{2} -\frac{48}{7}x+\frac{64}{7}[/tex]
Step-by-step explanation:
step 1
Find the roots of the quadratic equation
we know that
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]x^{2} -6x+7=0[/tex]
so
[tex]a=1\\b=-6\\c=7[/tex]
substitute in the formula
[tex]x=\frac{6(+/-)\sqrt{-6^{2}-4(1)(7)}} {2(1)}[/tex]
[tex]x=\frac{6(+/-)2\sqrt{2}} {2}[/tex]
[tex]x=3(+/-)\sqrt{2}[/tex]
[tex]x1=3(+)\sqrt{2}[/tex]
[tex]x2=3(-)\sqrt{2}[/tex]
The roots of the equation are a and b
so
[tex]a=3(+)\sqrt{2}[/tex]
[tex]b=3(-)\sqrt{2}[/tex]
step 2
Find a quadratic equation with roots a+1/b and b + 1/a
so
[tex]a+\frac{1}{b} =(3+\sqrt{2})+\frac{1}{3-\sqrt{2}} =\frac{9-2+1}{3-\sqrt{2}} =\frac{8}{3-\sqrt{2}}=\frac{8}{3-\sqrt{2}}*(\frac{3+\sqrt{2}}{3+\sqrt{2}})=\frac{8}{7}(3+\sqrt{2})[/tex]
[tex]b+\frac{1}{a} =(3-\sqrt{2})+\frac{1}{3+\sqrt{2}} =\frac{9-2+1}{3+\sqrt{2}} =\frac{8}{3+\sqrt{2}}=\frac{8}{3+\sqrt{2}}*(\frac{3-\sqrt{2}}{3-\sqrt{2}})=\frac{8}{7}(3-\sqrt{2})[/tex]
The quadratic equation is equal to
[tex]y=(x-\frac{8}{7}(3+\sqrt{2}))(x-\frac{8}{7}(3-\sqrt{2}))[/tex]
[tex]y=x^{2} -\frac{8}{7}(3-\sqrt{2})x-\frac{8}{7}(3+\sqrt{2})x+\frac{64}{49}(7)[/tex]
[tex]y=x^{2} -\frac{48}{7}x+\frac{64}{7}[/tex]